Adherence barriers to inhaled medicines in Japanese older patients with asthma evaluated using the "Adherence Starts with Knowledge 20" (ASK-20) questionnaire. (3rd June 2019) - Sasaki, Jun; Kawayama, Tomotaka; Yoshida, Makoto; Takahashi, Koichiro; Fujii, Kazuhiko; Machida, Kentaro; Kinoshita, Takashi; Hoshino, Tomoaki; ,
Abstract: Objective : We investigated adherence barriers to inhaled medicines among older compared to younger adults with asthma in Japan. Methods : Adherence barriers to inhaled medicines were evaluated in 251 Japanese older ( n = 138) and younger ( n = 113) adults with asthma using the self-reporting "Adherence Starts with Knowledge 20" (ASK-20) questionnaire. Results : There were fewer older adults with poor adherence to inhaled medicines than younger adults. The ASK-20 questionnaire revealed (odds ratio [95% confidence interval]) item Q11 ("My doctor/nurse and I work together to make decisions"; 2.94 [1.31, 6.61]; p < 0.05) as an independent adherence barrier to inhaled medicines among older adults, whereas younger adults reported item Q3 ("My use of alcohol gets in the way of taking my medicines"; 3.91 [1.02 to 15.1]; p < 0.05) and item Q16 ("Taken a medicine more or less often than prescribed? "; 2.31 [1.32 to 4.06]; p < 0.05) as barriers. Older adults with poor adherence identified item Q1 ("I just forget to take my inhaled medicines some of the time"; 4.43 [1.77, 11.1]; p < 0.05) as a barrier, although the total ASK-20 scores and total barrier counts were significantly higher in older (both, p < 0.05) and younger (both, p < 0.05) adults with poor adherence than in those with good adherence. Conclusion : Older Japanese patients had better adherence to inhaled medicines than younger patients. Barriers were different between older and younger adults. These results will help personalize education for inhaled medicines in Japanese asthmatics.